2022
DOI: 10.14421/biomedich.2022.112.151-160
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant, Anti-inflammatory and Anti-Atherosclerotic Activity of Bioactive Peptide HPAEDR Isolated from Catla catal Muscle on LPS Induced Inflammation on 246.7RAW Macrophage Cells and HCF Induced Hyperlipidemic Zebrafish Larvae

Abstract: A muscle wasdissected from the Catla catlafish and enzyme hydrolysis was done using various digestive enzymes such as pepsisn, protease, papine, trypsin and alcalase at verity of time intervals (0th, 3rd, 6th, 9th and 12th) hour respectively. Followed by, the amino acid composition was identified and the confirmative assays such as, the anti-oxidant assays (DPPH and Hydroxy radical scavenging activity) and anti-inflammatory assays (HRBC and AD) were done for various peptide hydrolysate. The active hr was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Currently, several studies have found that peptides derived from fish muscle exhibited anti-atherosclerotic and hepatoprotective activities to various degrees. The peptide HPAEDR isolated from catla muscle exhibited anti-atherosclerotic and anti-inflammatory activities in hyperlipidemic zebrafish [15].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several studies have found that peptides derived from fish muscle exhibited anti-atherosclerotic and hepatoprotective activities to various degrees. The peptide HPAEDR isolated from catla muscle exhibited anti-atherosclerotic and anti-inflammatory activities in hyperlipidemic zebrafish [15].…”
Section: Introductionmentioning
confidence: 99%
“…Fish-isolated low-molecular-weight bioactive peptide is a popular safe cosmetic biomaterial considered to be a good source of antioxidant and anti-inflammatory activities [ 45 , 46 , 47 , 48 ]. The antioxidant properties of hydrolyzed collagen are conditioned to the size of the molecule: the lower the molecular weight of peptides, the greater the ability to donate an electron or hydrogen to stabilized radicals [ 35 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%